The Importance of Determining the Drug Agent Responsible for Pancytopenia in Patients with Rheumatoid Arthritis and Additional Systemic Diseases - Hava Üsküdar TEKE,; Arzu Erdem TAŞDEMİR,; Mustafa ÖZEN3, (Archives of Rheumatology, 2013)
Methotrexate (MTX) is the most commonly used drug in the treatment of rheumatoid arthritis (RA). In MTXtreated RA patients, the prevalence of pancytopenia is nearly 3%. Several medications may be prescribed for RA patients with an additional systemic disease. This may result in bone marrow toxicity, making it difficult to know which drug induced the pancytopenic condition. Therefore, identifying the culprit agent through bone marrow aspiration and biopsy findings of the samples is critical for determining the best course of treatment for pancytopenia. Significantly increased amounts of eosinophilia in the bone marrow indicate that MTX is the culprit for the presentation of pancytopenia.